2018
DOI: 10.1038/s41598-018-35716-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 11 treatment leads to neuronal and vascular improvements in the hippocampus of aged mice

Abstract: Aging is the biggest risk factor for several neurodegenerative diseases. Parabiosis experiments have established that old mouse brains are improved by exposure to young mouse blood. Previously, our lab showed that delivery of Growth Differentiation Factor 11 (GDF11) to the bloodstream increases the number of neural stem cells and positively affects vasculature in the subventricular zone of old mice. Our new study demonstrates that GDF11 enhances hippocampal neurogenesis, improves vasculature and increases mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
81
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 66 publications
13
81
1
1
Order By: Relevance
“…The fact that systemic administration of GDF11 induced healthy weight loss as early as 1 week after treatment and subsequently reached a plateau comes to accordance with previous reports (Ozek et al, ; Poggioli et al, ). During and after the treatment, all mice were healthy and displayed no signs of cachexia or frailty contrary to previous reports (Egerman et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The fact that systemic administration of GDF11 induced healthy weight loss as early as 1 week after treatment and subsequently reached a plateau comes to accordance with previous reports (Ozek et al, ; Poggioli et al, ). During and after the treatment, all mice were healthy and displayed no signs of cachexia or frailty contrary to previous reports (Egerman et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, other reports argued that GDF11 was positively associated with aging, cachexia, and inhibition of muscle regeneration in aged mice (Egerman et al, ; Harper et al, ; Jones et al, ), while different studies showed a beneficial role for GDF11 in the periphery (Poggioli et al, ; Su et al, ; Walker et al, ). In the central nervous system, GDF11 was also shown to be neuroprotective for neurovascular recovery and neurogenesis (Anqi, Ruiqi, Yanming, & Chao, ; Ma et al, ; Ozek, Krolewski, Buchanan, & Rubin, ; Schafer & LeBrasseur, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma transfer experiments demonstrating rejuvenation following intravenous delivery of a relatively small volume of young plasma or serum into old mice (100-175 μl, 6-10 times over 2-4 weeks) 5,6,11,12 suggest that supplementation with youthful factors may be sufficient to promote cognitive health, both during healthy aging and in neurodegenerative disease. Systemic administration of Growth Differentiation Factor 11 (GDF11) increased the number of neural stem cells and improved vascular remodeling in the subventricular zone and hippocampus of aged mice 14,15 . GDF11 may not cross the blood-brain barrier but instead impact the brain parenchyma by enhancing vascular endothelial growth factor (VEGF) secretion by brain vascular endothelial cells 15 , thereby stimulating both angiogenesis and neurogenesis 16 .…”
Section: Delivery Of Youthful Factors To Promote Cognitive Healthmentioning
confidence: 99%
“…Systemic administration of Growth Differentiation Factor 11 (GDF11) increased the number of neural stem cells and improved vascular remodeling in the subventricular zone and hippocampus of aged mice 14,15 . GDF11 may not cross the blood-brain barrier but instead impact the brain parenchyma by enhancing vascular endothelial growth factor (VEGF) secretion by brain vascular endothelial cells 15 , thereby stimulating both angiogenesis and neurogenesis 16 . THBS4 and SPARCL1 may also be beneficial 9 if these factors are capable of crossing the blood-brain barrier to promote synapse formation and function.…”
Section: Delivery Of Youthful Factors To Promote Cognitive Healthmentioning
confidence: 99%